Genomic characteristics and antibiotic resistance profiles of monophasic Salmonella Typhimurium in Shaanxi Province, China - Shi, Yi; Liu, Yuguo; Li, Shen; Wu, Songwen; Ma, Guozhu; Luan, Yang; Zhang, Junjun; Chen, Yali; Liu, Wanjing; Shen, Tuo; Wang, Caiqiao; Xu, Jiru (Frontiers in Microbiology, 2025)
IntroductionMonophasic Salmonella Typhimurium, characterized by the absence of phase II flagellar antigens, has become increasingly prevalent as a foodborne pathogen, raising significant public health concerns due to its multidrug resistance. This study investigated the genomic characteristics and antibiotic resistance profiles of the monophasic Salmonella Typhimurium strains isolated from patients and food sources in Shaanxi Province, China.MethodsA total of 58 strains were collected between 2020 and 2021, with 4 strains isolated from food and 54 from patients. Whole genome sequencing was performed to assess genomic features. Antimicrobial susceptibility was tested against 17 antimicrobial agents using the broth dilution method, while pulsed-field gel electrophoresis (PFGE) and multi-locus sequence typing were employed for genetic characterization and epidemiological analysis. Phylogenetic analysis was conducted using single nucleotide polymorphism clustering.Results and discussionOur results revealed that all the strains belonged to the ST34 and did not carry virulence genes on pSLT (NC_003277). There were 12 strains carrying the STM2757 gene. The isolates exhibited a considerable diversity in PFGE subtypes. Phenotypic antimicrobial resistance showed that the strains were most resistant to tetracycline (94.34%; 50/53) and ampicillin (94.34%; 50/53), followed by streptomycin (88.68%; 47/53) and ampicillin/sulbactam (64.15%; 34/53). Resistance gene prediction highlighted the presence of 64 distinct genes, with aac(6’)-Iaa found in all strains (100%) and tet(B) in 93.1% of strains. Notably, the floR gene, relevant for resistance to phenicols, was observed in 44.83% of isolates. Genomic analysis revealed that 96.55% of strains were positive for the sodC1 virulence gene, whereas only 10.34% carried the sopE gene. The most plasmid replicon was IncQ1 (84.48%; 49/58), followed by IncHI2 (32.76%; 19/58) and IncHI2A (32.76%; 19/58). Single nucleotide polymorphism analysis showed that 2 strains were clustered together with SRR17830210 (UK outbreak isolate) with a bootstrap value of 0.949. There were only 12 allelic differences between SNXiAn21SAL011 and the reference strain. Conclusively, the monophasic Salmonella Typhimurium ST34 strains in Shaanxi Province demonstrated unique genomic and antimicrobial resistance traits. This study may help to prevent outbreaks and rationalize salmonellosis antimicrobial therapeutics.